Edentulism, beaks, and biomechanical innovations in the evolution of theropod dinosaurs - Lautenschlager, Stephan (National Academy of Sciences, 2013)
Maniraptoriformes, the speciose group of derived theropod dinosaurs that ultimately gave rise to modern birds, display a diverse and remarkable suite of skeletal adaptations. Apart from the evolution of flight, a large-scale change in dietary behavior appears to have been one of the main triggers for specializations in the bauplan of these derived theropods. Among the different skeletal specializations, partial or even complete edentulism and the development of keratinous beaks form a recurring and persistent trend in from the evolution of derived nonavian dinosaurs. Therizinosauria is an enigmatic maniraptoriform clade, whose members display these and other osteological characters thought to be correlated with the shift from carnivory to herbivory. This makes therizinosaurians prime candidates to assess the functional significance of these morphological characters. Based on a highly detailed biomechanical model of Erlikosaurus andrewsi, a therizinosaurid from the Upper Cretaceous of Mongolia, different morphological configurations incorporating soft-tissue structures, such as a keratinous rhamphotheca, are evaluated for their biomechanical performance. Our results indicate that the development of beaks and the presence of a keratinous rhamphotheca would have helped to dissipate stress and strain, making the rostral part of the skull less susceptible to bending and displacement, and this benefit may extend to other vertebrate clades that possess rhamphothecae. Keratinous beaks, paralleled by edentulism, thus represent an evolutionary innovation developed early in derived theropods to enhance cranial stability, distinct to postulated mass-saving benefits associated with the origin of flight.